2017
DOI: 10.1111/cdev.12837
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Sexting Behaviors and Sexual Behaviors Among Mobile Phone‐Owning Teens in Los Angeles

Abstract: The implications of teen sexting for healthy development continue to concern parents, academics, and the general public. Using a probability sample of high school students (N = 1,208) aged 12-18, the prevalence of sexting, associations with sexting, and associations between sexing and sexual activity were assessed. Seventeen percent both sent and received sexts, and 24% only received sexts. Sending and receiving sexts were positively associated with each other and both behaviors were associated with having pee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
39
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 27 publications
6
39
0
1
Order By: Relevance
“…Similar to previous studies (Rice et al 2018;Temple and Choi 2014;Ybarra and Mitchell 2014), we found that adolescents who had more previous sexual experiences were more likely to engage in sexting. Likewise, adolescents who had their first sexual contact at a younger age or had more sexual partners in their lifetime were more likely to have sent a sext.…”
Section: General Adolescent Sexting Sexual Behavior and Sexual Risksupporting
confidence: 90%
See 2 more Smart Citations
“…Similar to previous studies (Rice et al 2018;Temple and Choi 2014;Ybarra and Mitchell 2014), we found that adolescents who had more previous sexual experiences were more likely to engage in sexting. Likewise, adolescents who had their first sexual contact at a younger age or had more sexual partners in their lifetime were more likely to have sent a sext.…”
Section: General Adolescent Sexting Sexual Behavior and Sexual Risksupporting
confidence: 90%
“…Sending sexually explicit text messages has also been associated with subsequent sexual behaviors (Brinkley et al 2017). Crosssectional studies found that adolescents' engagement in sexting is linked with involvement in different types of sexual behavior (ranging from oral sex to vaginal or anal sex) (Houck et al 2014;Ybarra and Mitchell 2014;Rice et al 2018). Furthermore, the sending of self-made sexually explicit pictures among adolescents has been crosssectionally associated with sexual risk behaviors, including having a higher average number of sexual partners in the year prior to the study (Ybarra and Mitchell 2014;Temple et al 2012), using alcohol or drugs before sex (Temple et al 2012), and failure to use a condom during the last sexual intercourse (Rice et al 2018;Rice et al 2012).…”
Section: Associations Between Adolescent Sexting and Risk Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Survey studies have found that problematic cell phone use was related to substance abuse (Gallimberti et al, ); that nighttime text messaging was associated with sleeping less, more sleepiness during the day, and lower academic performance (Grover et al, ); and that exchanging a greater proportion of communication with romantic partners via text messages was related to lower interpersonal competence one year later (Nesi et al, ). Several studies have shown that sexting relates to risky sex (Brinkley, Ackerman, Ehrenreich, & Underwood, ; Choi et al, ; Rice et al, ).…”
Section: Empirical Investigations Of Adolescents’ Text Messagingmentioning
confidence: 99%
“…Prevalence was not moderated by geographic location but did increase with youths' age and by year of data collection. This rising trend of sexting among adolescents is thought to be coupled with the proliferation of smartphone ownership and increased texting habits [5]. As youth technology habits have shifted over time, so have scholarly discussions about the developmental utility of sexting, such that developmental perspectives are increasingly present in sexting research compared with early examinations of the topic [6].…”
mentioning
confidence: 99%